Sifax v. Migfo and Limitation Laws in Nigeria: Triumph of Pragmatism over Formalism?. Issue 4 (November 2020) - Olatoye, Kareem; Yekini, Abubakri
Abstract : The recent pronouncement of the Supreme Court of Nigeria in Sifax & Ors v. Migfo & Anor reveals the desirability of a pragmatic as against a formalistic approach to Nigerian limitation laws. This article critically examines Sifax and seizes the opportunity to flag up the inadequacies in the extant limitation laws in Nigeria. The article argues that a total overhaul of the limitation laws is long overdue as they are not only old-fashioned and ambiguous but also produce undesirable results. It predicts that it is very unlikely that any legislative intervention may be witnessed in the nearest future. Therefore the article suggests that the courts must continue to fill the gaps by a pragmatic interpretation of the laws within the bounds of the general policy objectives of the limitation laws. It advocates comparative judicialism as a useful methodology to achieve this task.